Application of the Cooperative Script Learning Model to Improve Student Learning Outcomes in Basic Competencies Understanding Various Styles in Building Structures at SMK Negeri 1 Lotu for the 2022/ 2023 Academic Year - Jeremy Fahela Zebua; Adrianus Zega; Envilwan Berkat Harefa (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
The problem in this study is that the Cooperative Script learning model has not been optimally applied to the Basic Competence of Understanding Various Styles in Building Structures and student learning outcomes are limited to achieving KKM, namely 70. Research objectives: (1) To describe the learning process by applying the Cooperative Script learning model on Basic Competency of Understanding Various Styles in Building Structures at SMK Negeri 1 Lotu for Academic Year 2022/2023, and (2) To find out student learning outcomes for Basic Competency for Understanding Various Styles in Building Structures at SMK Negeri 1 Lotu for Academic Year 2022 /2023. This type of research is Classroom Action Research (CAR). This research was conducted at SMK Negeri 1 Lotu with research subjects of class X DPIB, totaling 22 people. The instruments in this study were observation sheets of the learning process (teacher respondents), observation sheets of student activity, photo documentation, and learning achievement tests. With the data analysis technique, namely the observation sheet is processed with a Likert scale and the learning achievement test is carried out by validation test and test feasibility test. Research results: (1) In cycle I (First) the average percentage of observations in the learning process (teacher respondents) is 65.63%, the average percentage of observations of student activity is 48.44%, the average learning outcomes count is 65.78 with a percentage of student completeness of 45.45% and this result has not reached the target that has been set, namely 70. (2) While in cycle II (two) the average percentage of observations in the learning process (teacher respondents) is 87.50%, the average percentage of observations of student activity is 81.25%, the average student learning outcomes is 81.36 which is categorized as good with a complete percentage of student learning outcomes of 100% and has reached the set target of 70. From the research findings above it can be concluded that by applying the Cooperative Script learning model to the Basic Competency Engineering Mechanics subject of Understanding Various Styles in Building Structures can improve student learning outcomes at SMK Negeri 1 Lotu.